Intergenerational Effects of Paternal B vitamin Intake on DNA Methylation, Gene Expression, and Intestinal Tumorigenesis in the Apc1638N Mouse Model of Colorectal Cancer. - Sabet, Julia. (2017)
Abstract: Background: Evidence is emerging that paternal diet influences various aspects of offspring health, although the underlying mechanisms are unclear and studies of the effects of paternal diet on offspring risk of cancer are lacking. We aim to investigate the extent to which diet-induced DNA methylation patterns are transmitted from father to offspring and whether paternal diet alters offspring risk of cancer. Dietary folate and related B vitamins have been shown to reduce the risk of colorectal cancer, and recently we have shown in a mouse model of colorectal cancer (APC1638N) that supplemental intake of vitamins B6, B12, riboflavin and folate by mouse dams reduced the risk of cancer in offspring, while deficient intake of these vitamins increased the aggressiveness of cancer in offspring. In the present study, we hypothesized that similar effects could be observed by modulating B vitamin intake in the paternal diet. Methods: Weanling male Apc1638N mice were pair-fed diets containing replete, deficient, or supplemental quantities of vitamins B6, B12, riboflavin and folate for 8 weeks before mating with control-fed C57BL/6J wild type females. Wild type offspring were sacrificed at weaning and their livers were used for RNA-Seq genome-wide expression analysis. Apc1638N offspring were maintained on a replete diet until 28 weeks of age, at which point blood and liver were collected for metabolic analyses and small intestines were scrutinized for the presence of tumors. Results: Hundreds of changes in DNA methylation were observed in the sperm of fathers consuming either a B vitamin deficient or B vitamin supplemented diet compared to control, and changes in genome-wide hepatic expression were found in their weanling offspring, but very few genes were both differentially methylated in fathers and differentially expressed in offspring. No differences in intestinal tumor incidence, size or grade were found between Apc1638N offspring of different paternal diet groups; however male offspring overall exhibited higher tumor incidence and severity of phenotype compared to females. Furthermore, mice bearing tumors were heavier than those without - a differential effect that began at 7 weeks and persisted until the experiment ended at 28 weeks. Unexpectedly, both B vitamin deficient and B vitamin supplemented fathers had lower body weight compared to control, as did their female offspring. Finally, female offspring of supplemented fathers had greater hepatic triglyceride content compared to control. Conclusions: Our results do not support the hypothesis that changes in sperm DNA methylation patterns induced by dietary B vitamin modulation are passed on to the next generation, nor do they support the hypothesis that paternal B vitamin intake impacts on offspring tumorigenesis in the Apc1638N mouse model of colorectal cancer. We do, however, show that modulation of paternal B vitamin intake impacts on body weight and lipid metabolism in offspring in a sex-specific fashion. Further work is required to fully elucidate the importance of paternal exposures in programming offspring health and physiology.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Jimmy Crott.; Committee: Edward Saltzman, Joel Mason, and Xiang-Dong Wang.; Keyword: Nutrition.